Drug-induced liver injuries - S. F. Galimova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate modern concept on management and prevention in patients with drug-induced liver injury (DILI).Key points. DILI have a wide spectrum of clinical symptoms, from asymptomatic elevation of serum transaminase activity to fulminant liver failure. The task of clinician – to withdraw a «causative» drug and under indications to prescribe specific and/or symptomatic treatment in due time. Preventive measures include global control of clinical and postmarketing investigations. Observation of mode of intake of the drug, analysis of risk factors, polypragmasy, drug interactions, carrying out of appropriate investigation at prescription of potentially hepatotoxic drugs lays at the basis of prevention concerning the specific patient.